Contribution of passive actions to the lower limb joint moments and powers during gait: A comparison of models. (August 2018) - Gasparutto, Xavier; Jacquelin, Eric; Dumas, Raphael
The lower limb passive actions representing the actions of all the passive periarticular structures have been shown to have a significant contribution to the power generation and absorption during gait. However, the respective magnitude of its different components was not established, although models of ligament moment were implemented in some musculoskeletal models. These ligament moments have shown to have an influence on the musculo-tendon forces and contact forces but the models used were never specifically evaluated, that is, compared to the passive and net joint moments. Two models of passive joint moments and three models of ligament moments were selected from the literature. Ten subjects (23–29 years old, 79.8 ± 9.5 kg, 1.85 ± 0.06 m) participated in the study. Each subject performed three gait cycles in a gait laboratory to acquire the kinematics and ground reaction forces and to compute the ligament, passive and net moments of the right lower limb joints. The contributions of the passive joint moments to the net joint moments were in accordance with the literature, although time shifts appeared for peaks in the hip and knee powers. Two of the models of ligament moments seemed, in fact, to represent the passive joint moments as their contributions were very similar while the third model of ligament moments seemed to represent only penalty-based joint limits. As a conclusion, this study showed that the models of ligament moments existing in the literature do not seem reliable. This study also demonstrated that the use of non-subject-specific models of the passive joint moments could be a valid approach for healthy subjects.